2010
DOI: 10.1063/1.3480547
|View full text |Cite
|
Sign up to set email alerts
|

Instability in threshold voltage and subthreshold behavior in Hf–In–Zn–O thin film transistors induced by bias-and light-stress

Abstract: Electrical bias and light stressing followed by natural recovery of amorphous hafnium-indium-zinc-oxide (HIZO) thin film transistors with a silicon oxide/nitride dielectric stack reveals defect density changes, charge trapping and persistent photoconductivity (PPC). In the absence of light, the polarity of bias stress controls the magnitude and direction of the threshold voltage shift (ΔVT), while under light stress, VT consistently shifts negatively. In all cases, there was no significant change in field-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 22 publications
(15 reference statements)
1
60
0
Order By: Relevance
“…[20][21][22][31][32][33][34] Chong et al reported that amorphous Hf-InZnO TFTs exhibited a small positive V th shift of about 1.8 V after BS for 60 h. However, even though there are positive reports on the high stability of OxTFTs, an issue originating from Zn has also been reported. Liu et al reported that hydrogen ions dissociate from the ZnO-H bonds in InGaZnO TFTs, resulting in an instability under BS.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…[20][21][22][31][32][33][34] Chong et al reported that amorphous Hf-InZnO TFTs exhibited a small positive V th shift of about 1.8 V after BS for 60 h. However, even though there are positive reports on the high stability of OxTFTs, an issue originating from Zn has also been reported. Liu et al reported that hydrogen ions dissociate from the ZnO-H bonds in InGaZnO TFTs, resulting in an instability under BS.…”
mentioning
confidence: 95%
“…In the above results, group IV elements (such as Ti, Zr, Sn and Hf) play an important role in suppressing the excess charge carrier generation and improving the stability of the TFTs by binding with oxygen. [18][19][20][21][22][23][24][25] For InZnO incorporated with Si, a 3.7 V shift in the threshold voltage (V th ) after 6.5 h was reported. 23 Because of the lower interfacial trap density, the Zr-InZnO TFTs annealed at 350…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of bond strength to oxygen atoms, Hf doping is also expected to have similar effects to Si doping. [31][32][33] However, to clarify the carrier transport in the present InO xbased semiconductors based on thermal activation, energy band diagrams, and local atomic structure, we will discuss further characterization, such as low temperature I-V measurements, 34 Hall measurements, 35,36 and X-ray absorption spectroscopy, 13,37 in another report. In conclusion, we fabricated amorphous oxide TFTs based on InO x semiconductors doped with Ti, W, or Si atoms.…”
mentioning
confidence: 99%